Multimode ultrasonic extraction of polysaccharides from maca (Lepidium meyenii): Optimization, purification, and in vitro immunoregulatory activity - Guo, Lina; Kong, Na; Zhang, Xinyan; Ma, Haile (Ultrasonics sonochemistry, 2022)
[Display omitted] •Multimode ultrasound extraction raised the polysaccharide (LMP) yield efficiently.•The highest yield of LMP was achieved with 20/35 alternation ultrasound treatment.•The composition of LMP extracted by ultrasonic was arabinose, galactose, glucose.•Purified LMP treated with ultrasound exerted remarkable immunoregulatory activity. This study evaluates the effect of multimodal ultrasound on the extraction efficiency and immunoregulatory activity of polysaccharides from Lepidium meyenii Walp. (LMP). The separation and purification of maca polysaccharides were investigated by the DEAE-52 cellulose column, and the monosaccharide compositions were identified by HPGPC. Their immune activity was analyzed by the secretion of cytokines (TNF-α and IL-6) from RAW 264.7 macrophage. The results showed that the optimal extraction conditions were energy aggregation alternation dual-frequency ultrasound (EADU) with frequency combinations of 20/35, extraction time of 15 min, material/water ratio of 1:10 g/mL, ultrasonic power intensity of 150 W/L, intermittent time ratio of 4 s/3 s, and extraction temperature of 50 ℃. The extraction rates of purified polysaccharides (US3) increased by 44.90%. The LMP extracted by EADU contained arabinose, galactose, and glucose in the molar ratios of 2.9:2.72:5.05. In addition, US3 promoted the release of TNF-α and IL-6 from RAW 264.7 better than RS3 (purified polysaccharides extracted by hot water), which indicated that US3 exerted remarkable immune activity. It could be an excellent functional additive in food or medicine.